2021
DOI: 10.3389/fbioe.2021.732271
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of a Wheat Sidestream for 5-Aminovalerate Production in Corynebacterium glutamicum

Abstract: Production of plastics from petroleum-based raw materials extensively contributes to global pollution and CO2 emissions. Biotechnological production of functionalized monomers can reduce the environmental impact, in particular when using industrial sidestreams as feedstocks. Corynebacterium glutamicum, which is used in the million-ton-scale amino acid production, has been engineered for sustainable production of polyamide monomers. In this study, wheat sidestream concentrate (WSC) from industrial starch produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…After CoQ 10 production was successfully improved, the strain UBI6-Rs was cultivated with a hydrolysate of the alternative feedstock wheat side stream concentrate (WSCH) [ 40 ]. In a sustainable circular economy, side streams of industrial production processes can provide excellent alternative feedstocks for microbial production containing macro- and micronutrients [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After CoQ 10 production was successfully improved, the strain UBI6-Rs was cultivated with a hydrolysate of the alternative feedstock wheat side stream concentrate (WSCH) [ 40 ]. In a sustainable circular economy, side streams of industrial production processes can provide excellent alternative feedstocks for microbial production containing macro- and micronutrients [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…With respect to alternative feedstocks that are not competitive with food or feed, C. glutamicum has been employed and engineered for many different substrates. Here, we demonstrated the successful production of CoQ 10 from a wheat side stream-based hydrolysate that has been utilized previously for the production of 5-aminovalerate [ 40 ] and l -2-hydroxyglutarate [ 22 ]. As well as the wheat side stream, access to numerous monomeric and polymeric carbon sources has been established, e.g., xylose, arabinose, mannose, starch, lignocellulose, N -acetylglucosamine, and alginate, which can be derived from hydrolysates of sustainable second generation feedstocks such as spent sulfite liquor, Miscanthus biomass, brown seaweed, corn straw, rice straw, and shrimp waste [ 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with the results of the fecal metabolome analysis in which parishin treatment reversed the aging-induced depletion of 3-(3-hydroxyphenyl)-propanoic acid, L-proline, 4-hydroxybenzeneacetic acid and 5-aminovaleric acid. 5-Aminovaleric acid, the γ-aminobutyric acid (GABA) analog, is an important intermediate in the pathways of L-lysine degradation and L-proline degradation ( Burgardt et al, 2021 ; Cheng et al, 2021 ); the microbial flavonoid metabolite 4-hydroxybenzeneacetic acid, which possesses anxiolytic effects, is generated from gut microbial polyphenol and amino acid metabolism, and is an important intermediate in the pathways of L-tyrosine degradation and automatic biogenic amine degradation ( Zabela et al, 2016 ; Orabi et al, 2021 ); 3-(3-hydroxyphenyl)-propanoic acid, which has been reported to exhibit hepatoprotective activities by regulating oxidative stress, lipid peroxidation, and inflammatory responses ( Cui et al, 2018 ), is an intermediate in the phosphatidylcholine resynthesis pathway and in the mitochondrial NADPH production pathway of the cofactor, carrier, and vitamin biosynthesis superfamily. In addition, the parishin treatment-improved metabolite β-sitosterol is a plant-derived natural bioactive compound with various pharmacological activities, such as hypolipidemic, anti-inflammatory, antitumor, tissue repair and antiaging activities ( Haiyuan et al, 2019 ; Cheng et al, 2020 ), and is used to treat fatty liver, type II diabetes, and arthritis ( Gumede et al, 2020 ; Ramalingam et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…glutamicum consortium has been engineered for growth and production with starch ( Sgobba et al, 2018b ). The remaining challenges are that starchy biomass does have competing uses as food and feed, that debranching enzymes such as pullulanase have to be secreted or that starch has to be hydrolyzed to access cyclodextrin and branched starch portions ( Burgardt et al, 2021 ).…”
Section: Engineering Corynebacterium Glutamicum Fo...mentioning
confidence: 99%